2020
DOI: 10.21831/jrpm.v7i1.31221
|View full text |Cite
|
Sign up to set email alerts
|

Bagaimana hasil penyetaraan paket tes USBN pada mata pelajaran matematika dengan teori respon butir?

Abstract: Dalam melakukan standarisasi pendidikan di Indonesia maka dilakukan Ujian Sekolah Berstandar Nasional (USBN).Karena perangkat tes yang digunakan dalam USBN tersebut sebagian besar butir tesnya dikembangkan oleh guru, perangkat tes yang diujikan kepada siswa di daerah yang satu akan berbeda dengan daerah yang lainnya meskipun sama-sama mengacu pada kisi-kisi dari pemerintah. Oleh karena itu perlu dilakukan penyetaraan perangkat tersebut. Penelitian deskriptif eksploratif dengan pendekatan kuantitif ini bertujua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Of the four equalization methods used, it was found that equalization using the Stocking-Lord method produced the most equivalent scores between packages. These findings are the same as those of previous studies (Uysal & Kilmen, 2016) but different from the findings of other studies (Yusron et al, 2020a). This indicates that the literature has not been able to provide strong evidence that one method is better than the other equalization methods.…”
Section: Figure 2 Test Characteristic Curve Equating For All Equating...supporting
confidence: 56%
See 2 more Smart Citations
“…Of the four equalization methods used, it was found that equalization using the Stocking-Lord method produced the most equivalent scores between packages. These findings are the same as those of previous studies (Uysal & Kilmen, 2016) but different from the findings of other studies (Yusron et al, 2020a). This indicates that the literature has not been able to provide strong evidence that one method is better than the other equalization methods.…”
Section: Figure 2 Test Characteristic Curve Equating For All Equating...supporting
confidence: 56%
“…The difference in findings between studies is very likely due to differences in several things, such as the characteristics of the test takers and the types of test items. For example, the study by (Yusron et al, 2020a) used a test kit for high school level students. This study is clearly different from our study, in which we used a test for junior high school students.…”
Section: Figure 2 Test Characteristic Curve Equating For All Equating...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods have more moderate error estimates, and the results are more accurate when using more anchor items (Born et al, 2019). Similarly, Yusron, Retnawati, and Rafi (2020) show that the Haebara method can produce the smallest average RMSE compared to the mean-mean, mean-sigma, and Stocking Lord methods.…”
Section: Introductionmentioning
confidence: 71%
“…Based on IRT, there are three testing equivalence designs that were employed: i) Anchor testing design; ii) Equivalent group design; and iii) Single group design [36]. In an equivalent group design, two tests were done to two equivalent groups drawn randomly from the same population (presumed that they had the same level of ability) [37], [38]. The equivalent group design may not only lessen the impact of activity and boredom, but it may also cause bias since the groups' levels of ability were probably not equivalent [39].…”
Section: Introductionmentioning
confidence: 99%